The divine sense : the intellect in patristic theology - Williams, A. N. (Anna Ngaire) (New York : Cambridge University Press, 2007)
"In the first book-length treatment of this subject, A.N. Williams examines the conception of the intellect in patristic theology from its beginnings in the work of the Apostolic Fathers to Augustine and Cassian in the early fifth century."--Jacket.
The dawn of Christian theology -- Early Alexandrians : Clement and Origen -- Cappadocian theology : Nazianzen and Nyssen -- Augustine -- Monastic writings.
Includes bibliographical references (pages 240-249) and index.
Keywords: Theology -- History -- Early church, ca. 30-600.; Church history -- Primitive and early church, ca. 30-600.; Intellectual life -- History